Modelagem e simulação de um secador intermitente de fluxos contracorrentes para frutos do cafeeiro - Joaquin, Tito Nahun Mancilla (2015)
This work was carried out in order to develop a computer model to simulate the drying of coffee fruits in an intermittent counter-flow dryer, using the Extend™ simulation language and Thompson Model (THOMPSON; PEART; FOSTER, 1968). For model validation were used experimental data obtained by Silva (1991), that worked with three air drying temperatures 60, 80 and 100 °C. The model was validated with absolute deviation of 1,8% b.u. and 1,1 kg and relative error of 11% and 1,6% for predicting final water content and firewood consumption, respectively. The validated model was employed in simulation experiments type scenario comparison. The first experiment concerns to operating cycle considering changes in handling and stop times of grain mass flow. The second relates to dryer configuration considering different heights of drying and tempering sections. The operating cycle with handling time of one minute and stop time of sixteen minute, using drying air temperature of 100 °C, results in the best performance of the dryer, with drying time of 12.3 h, firewood consumption of 109.5 kg, specific energy consumption of 7,660 kJ per kg of evaporated water, and drying capacity of 87.86 kg per hour. In relation to the dryer configuration, the best performances occurred for drying chamber with height of 2.3 m, using drying air temperature of 100 °C, when it was simulated drying time 12.0 h, firewood consumption 106.5 kg, specific energy consumption 7,433 kJ per kg of evaporated water and drying capacity of 90 kg per hour. Thus, for drying coffee fruits using an intermittent counter-flow dryer, it is recommended operating cycle with handling time of one minute and stop time of sixteen minute, and not to use the tempering sections. This conclusion is based on dryer performance parameters. It is important to highlight that impact on quality parameters was not simulated.